The Production of Lightweight Aggregates from Local Wastes - Khairul Nizar, Ismail, Dr.; Mohd Sobri, Idris; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Sabarudin, Mohd; Khairun Azizi, Mohd Azizli (International Exhibition of Inventions, 2010)
Dr. Khairul Nizar Ismail and his team won gold at 35th International Exhibition of Inventions of Geneva, 18th - 22nd April 2007 organized by International Exhibition of Inventions on 18th - 22nd April 2007 at Palexpo Hall 7, Geneva, Switzerland.